Cockatoo, too - Murguia, Bethanie Deeney (Little Bee Books, 2016)
"Two cockatoos meet two more cockatoos in tutus and two tutued toucans. And then two more! Can they all can-can? They can! The cockatoos and toucans join together for a dance and ask the reader: 'Can you can-can too?'"--